2011
DOI: 10.1016/j.hivar.2010.12.004
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-related stigma and access to HIV treatments by people living with HIV/AIDS: A case study of selected states in North-West Nigeria

Abstract: a b s t r a c tObjectives: To study the prevalence of HIV-related stigma and the effect of stigma on HIV treatment adoption among PLWHA attending HIV treatment locations in some selected states in the North-West geopolitical zone of Nigeria. Methods: A cross-sectional survey was conducted (using structured questionnaires) among PLWHA in three selected states in the North-West geopolitical zone of Nigeria and Abuja, the Federal Capital Territory (FCT). The multiple logistic regressions analysis was used to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…Home visitation or the provision of food supplements that might publicly label PLWHAs were unwelcome because of the potential negative consequences should the interventions be witnessed by others. Akpa, Adeolu-Olaiya, Olusegun-Odebiri, and Aganaba (2011) reported that more than half of PLWHAs in their study in Nigeria were unable to disclose their HIV status to family members or at their place of employment because of fears of stigmatization. Unique to this study, we found that nurses sometimes employ extraordinary measures to avoid such consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Home visitation or the provision of food supplements that might publicly label PLWHAs were unwelcome because of the potential negative consequences should the interventions be witnessed by others. Akpa, Adeolu-Olaiya, Olusegun-Odebiri, and Aganaba (2011) reported that more than half of PLWHAs in their study in Nigeria were unable to disclose their HIV status to family members or at their place of employment because of fears of stigmatization. Unique to this study, we found that nurses sometimes employ extraordinary measures to avoid such consequences.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this study, higher rates of negative reactions (20.5%) were reported in Southeast Nigeria. [ 17 ] Fortunately, few (1.4%) of them experienced physical violence upon disclosure unlike the 30% reported among women in Northern Nigeria,[ 28 ] and in Uganda, where 29.3% of the respondents reported intimate partner violence following disclosure of seropositive status to their partners. [ 29 ] This difference may have religious and cultural undertones.…”
Section: Discussionmentioning
confidence: 99%
“…Ada 11 artikel yang menganalisis stigma intrapersonal. Pasien HIV/AIDS merasa berbeda dari orang lain, kesepian, malu, kecewa pada diri sendiri, tidak dapat memiliki kehidupan yang memuaskan, dan merasa bersalah (Adjei et al, 2018;Akpa et al, 2011;Opollo & Gray, 2015;Pickles et al, 2017;Shilovskaya, 2015;Wu et al, 2015). Lebih lanjut, pasien ebola mengalami stigma internalisasi seperti merasa menjadi orang jahat, tidak bersih, dan merasa lebih buruk dari orang lain (James et al, 2020;Overholt et al, 2018).…”
Section: Stigma Intrapersonalunclassified
“…Ada 15 artikel yang menganalisis stigma interpersonal. Penderita HIV/AIDS mengalami penghindaran, pengucilan sosial, perlakuan buruk seperti pelecehan verbal dari masyarakat, dan tidak mendapat dukungan dari keluarga (Adjei et al, 2018;Akpa et al, 2011;Opollo & Gray, 2015;Pickles et al, 2017;Shilovskaya, 2015;Wu et al, 2015). Lebih lanjut, pasien ebola mengalami stigma yang diberlakukan seperti penghindaran publik, isolasi sosial, dan pelecehan.…”
Section: Stigma Interpersonalunclassified
See 1 more Smart Citation